Erratum for: Micropropulsion generation model and simulation by WGM acceleration within a panda ring resonator system - R. Siriroj; W. Techidheera; P. Phatharacom; S. Chiangga; P. Yupapin (My University, 2017)
Received 9 July 2016 In the above-mentioned article, which appeared in Microwave and Optical Technology Letters, Volume 59#2, DOI 30309, incorrect affiliation information was published for author P. Yupapin. The correction is shown below: 3Department for Management of Science and Technology Development, Ton Duc Thang University, District 7, Ho Chi Minh City, Vietnam 4Faculty of Electrical & Electronics Engineering, Ton Duc Thang University, District 7, Ho Chi Minh City, Vietnam Corresponding author: preecha.yupapin@tdt.edu.vn The publisher regrets any confusion caused by this error.
Keywords: Ho chi minh; Confusion; Plasma Diagnostics and Applications